Feelings of the mothers with babies hospitalized in neonatal intensive care unit - Ana Luiza Santos de Carvalho; Ana Cândida Serafim dos Reis; Flávia Regina Dias; Maria Adelane Alves Monteiro; Ana Karina Bezerra Pinheiro (Rev Rene)
This study aimed at understanding the feelings of the puerperas with babies hospitalized in neonatal intensive care unit. This is a descriptive exploratory research with qualitative approach accomplished with six mothers whose babies were hospitalized in neonatal intensive or intermediate care unit in a maternity hospital in Fortaleza, Ceará. The information were obtained through structured individual interviews and displaced in two categories of analysis: Feelings that emerge from the discovery that the newborn will need hospitalization and those experienced during the process of hospitalization of the newborn. We conclude that a mother who is experiencing the hospitalization of a newborn child needs effective care as a means of obtaining a better way of facing such a crisis, avoiding this that such a situation bring damage to the physical and emotional health of the mother